2007
DOI: 10.1097/bsd.0b013e318030a81d
|View full text |Cite
|
Sign up to set email alerts
|

Failure of the Wallis Interspinous Implant to Lower the Incidence of Recurrent Lumbar Disc Herniations in Patients Undergoing Primary Disc Excision

Abstract: The current Wallis implant is probably incapable of reducing the incidence of recurrent herniations, but it still may be useful in patients with discogenic back pain due to early degenerative disc disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 14 publications
0
35
0
1
Order By: Relevance
“…Though all the postoperative ODI means never reached the level of the CG population, for the majority of patients moderate disability was estimated. Our mid-term results suggest of substantial improvement in 1-2 years of observation attributed to studies [17,37,45], however, coincide with those short-term ones [6,7,41].…”
Section: Discussionmentioning
confidence: 42%
“…Though all the postoperative ODI means never reached the level of the CG population, for the majority of patients moderate disability was estimated. Our mid-term results suggest of substantial improvement in 1-2 years of observation attributed to studies [17,37,45], however, coincide with those short-term ones [6,7,41].…”
Section: Discussionmentioning
confidence: 42%
“…4,7,10,19,32,45,47,49,51 In our study, the overall reoperation rate was 9.6%: We performed removal of the interspinous spacer and decompressive surgery in 24 patients, additional instrumented fusion with pedicle screws in 63 cases, removal of the interspinous spacer only in 8 cases, and insertion of a new interspinous implant in 12 cases. We removed the IPD with no further spinal fixation or decompression in older patients with multiple comorbidities in whom major spinal surgery could have been life threatening.…”
Section: Discussionmentioning
confidence: 99%
“…Floman et al [6] used the Wallis device after primary disc excision in the hope of reducing recurrent disc herniation. In their non-randomized study, they found the implant to probably be incapable of reducing the incidence of recurrent herniation.…”
Section: Discussionmentioning
confidence: 99%